1986
DOI: 10.1099/00222615-21-2-139
|View full text |Cite
|
Sign up to set email alerts
|

Rare occurrence of Proteus vulgaris in faeces: a reason for its rare association with urinary tract infections

Abstract: Summary. The faecal carriage rates of different species of Proteeae were assessed in studies with 220 faecal isolates from 2 19 individuals of whom approximately one-third were well and the remainder had gastro-enteritis. As a result of the development of new media that allowed replacement of the phenylalanine deaminase test with the tryptophan deaminase test and made it possible to combine tests for indole and urease production and for hydrogen sulphide and ornithine decarboxylase formation in two single-tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…After overnight incubation at 37"C, strains which formed tryptophan deaminase (Senior and Leslie, 1986) and urease but failed to form acid from mannose were identified as Proteus spp. Those which formed tryptophan deaminase and acid from mannose were identified as species of either Morganella or Prouidencia.…”
Section: Identijication Of Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…After overnight incubation at 37"C, strains which formed tryptophan deaminase (Senior and Leslie, 1986) and urease but failed to form acid from mannose were identified as Proteus spp. Those which formed tryptophan deaminase and acid from mannose were identified as species of either Morganella or Prouidencia.…”
Section: Identijication Of Strainsmentioning
confidence: 99%
“…Modified New York City medium (MNYC) was prepared according to the method of Young (1978) but with horse blood (Oxoid SR 50). Tryptophan deaminase agar (TDA), urea-indole medium, ornithine decarboxylase-H2S medium and peptone-water sugar media were prepared and sterilised as previously described (Senior and Leslie, 1986).…”
Section: Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…After sterilisation as above, horse red-blood cells (Oxoid SR50) were added to give a final concentration of 5% v/v. Tryptophan deaminase agar medium, urealindole medium, ornithine decarboxylase/H,S medium and peptone-water sugar media were prepared and sterilised as previously described (Senior and Leslie, 1986). Saline was 0.85% NaCl in water.…”
Section: B W Senior and C Hughesmentioning
confidence: 99%
“…However, other members of the tribe Proteeae are rarely associated with urinary-tract infections and some are more often associated with diarrhoea (Senior, 1979(Senior, , 1983Senior and Leslie, 1986). Since Peerbooms et al (1983) have shown that the haemolysins produced by P. mirabilis influence the virulence of this organism for the mouse, we have investigated the frequency and characteristics of haemolysin production in clinical isolates of this and all other species in the Proteeae to see if the virulence of P. mirabilis for the urinary tract is likely to be similarly linked to haemolysin production.…”
Section: Introductionmentioning
confidence: 99%